Optimised radar processors - Farina, A. 1948- (IEE radar, sonar, navigation, and avionics series, 1987)
The first volume in a new series. Contributed papers give a theory of radar signal processing at a level accessible and useful to practicing radar engineers concerned with design and analysis. No index. Annotation(c) 2003 Book News, Inc., Portland, OR (booknews.com).